Numerically-based method for fracture characterization of Mode I-dominated two-dimensional delamination in FRP laminates. (15th April 2019) - Cameselle-Molares, Aida; Vassilopoulos, Anastasios P.; Renart, Jordi; Turon, Albert; Keller, Thomas
Abstract: A new numerically-based method suitable for determining the total strain energy release rate (SERR) involved in two-dimensional (2D) Mode I-dominated delamination under opening loads in FRP laminates is presented. The method is based on the mutual dependence of the load vs opening displacement curves slope exhibited after the full development of the fracture process zone (FPZ) and the total SERR involved in the delamination process. The equation relating these parameters is derived from three-dimensional finite element analyses performed using simple linear-softening cohesive zone models. Considering that the load-displacement curve reflects the overall fracture behavior, the above-mentioned slope correlates with the mean total SERR required to propagate the total 2D crack, independently of any local total SERR's variation along the crack front. Thus, the same mean cohesive zone model is used in all directions. By substituting the corresponding experimental slope of the load-displacement curves in the derived equation the total SERR is obtained. The method was validated using the experimental results from three types of GFRP/epoxy laminates with different fiber architectures. The measurement of the crack front is not required and the method is valid for any fiber architecture, crack shape and boundary conditions in Mode I-dominated and opening loading cases.